2022
DOI: 10.1002/advs.202203782
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Level Defect Structure Engineering for Unusually High Average Thermoelectric Figure of Merit in n‐Type PbSe Rivalling PbTe

Abstract: Realizing high average thermoelectric figure of merit (ZTave) and power factor (PFave) has been the utmost task in thermoelectrics. Here the new strategy to independently improve constituent factors in ZT is reported, giving exceptionally high ZTave and PFave in n‐type PbSe. The nonstoichiometric, alloyed composition and resulting defect structures in new Pb1+xSe0.8Te0.2 (x = 0–0.125) system is key to this achievement. First, incorporating excess Pb unusually increases carrier mobility (µH) and concentration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…8,19−25 V −1 s −1 and electron concentration to an optimal value of ∼2.0 × 10 19 cm −3 via introducing excess Pb, thereby noticeably raising the electrical conductivity (σ). 26 In this work, we find that doping a dilute amount of Te at Se sites of the Pb 0.97 Sn 0.01 Na 0.02 Se sample can achieve defect reconfiguration and significantly decrease the Pb vacancy concentration. Through the X-ray photoelectron spectroscopy (XPS) study, scanning transmission electron microscopy (STEM) measurement, and formation enthalpy calculation, we can demonstrate that doping Te will lead to a chemical reduction of Sn 4+ to Sn 2+ by pairing with Sn atoms.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…8,19−25 V −1 s −1 and electron concentration to an optimal value of ∼2.0 × 10 19 cm −3 via introducing excess Pb, thereby noticeably raising the electrical conductivity (σ). 26 In this work, we find that doping a dilute amount of Te at Se sites of the Pb 0.97 Sn 0.01 Na 0.02 Se sample can achieve defect reconfiguration and significantly decrease the Pb vacancy concentration. Through the X-ray photoelectron spectroscopy (XPS) study, scanning transmission electron microscopy (STEM) measurement, and formation enthalpy calculation, we can demonstrate that doping Te will lead to a chemical reduction of Sn 4+ to Sn 2+ by pairing with Sn atoms.…”
Section: Introductionmentioning
confidence: 70%
“…The same awkward situation has also been found in n-type PbSe, in which μ is only ∼20 cm 2 V –1 s –1 at 300 K on account of Pb vacancy scattering against carriers. , Incorporating extra metal atoms to occupy the remaining Pb vacancies is an effective and widely hired method to inhibit the Pb vacancies and recover μ. , For instance, Ge et al simultaneously improved the electron mobility to a splendid value of 635 cm 2 V –1 s –1 and electron concentration to an optimal value of ∼2.0 × 10 19 cm –3 via introducing excess Pb, thereby noticeably raising the electrical conductivity (σ) . Likewise, Qian et al obtained high μ and astonishingly low κ lat in n-type PbSe by, respectively, incorporating extra Cu, Zn, and Ni atoms. , Despite the clear efficiency of incorporating extra metal atoms in restraining Pb vacancies, interstitial metal atoms and secondary metallic phases can both produce extra electrons to neutralize the holes in p-type Sn-doped PbSe, causing degradation of σ.…”
Section: Introductionmentioning
confidence: 78%
“…However, the TEM studies have revealed that a substantial degree of nanostructures with a compositional fluctuation is embedded in the surrounding matrix in these materials. ,, The importance of atomic-resolution analysis to properly confirm the solid solution nature is highlighted by these observations. Nanostructures have unique interactions with charge carriers and phonons, which greatly impact the electrical and thermal properties of the bulk materials. , …”
Section: Resultsmentioning
confidence: 99%
“…Note that Pb metal shows significantly higher electrical conductivity than the PbSe matrix. [39][40][41][42] Its presence can give high electrical thermal conductivity, which is detrimental to the thermoelectric performance of the materials. As a result, the Energy & Environmental Science Paper concentration and size of excess Pb precipitates should be controlled by observing the thermoelectric performance of samples.…”
Section: Design Principle and Crystal Structurementioning
confidence: 99%